Spiritual Anomie in Gen Z: AI as A Medium for Spiritual Reflection for Islamic Students - Salsabila Anfang Mahadewi (UIN Sjech M. Djamil Djambek Bukittinggi, 2026)
The development of artificial intelligence presents a new space for Muslim students to engage in spiritual reflection. This phenomenon marks a shift in religious practices from communal spaces to digital ones, following a decline in trust in socio-religious relationships perceived as potentially judgmental. This study specifically analyzes the use of AI as a medium for spiritual outpouring, its role in self-reflection, the formation of Muslim students' spiritual identity, and its implications for social and religious relations in the digital era. Employing a qualitative-phenomenological approach, data were collected through in-depth interviews with three UIN Jakarta students utilizing AI for religious discussions. Data were collected through in-depth interviews with three UIN Jakarta students utilizing AI for religious discussions. Findings were analyzed using Émile Durkheim’s concept of anomie, Anthony Giddens’s reflexive identity, and Heidi Campbell’s networked religion. The results suggest that AI is used as a temporary safe space for spiritual outpouring while simultaneously aiding self-reflection and individual identity formation. These findings also reveal a shift in religious reflection toward more limited spheres. Furthermore, the research emphasises the importance of students’ critical thinking in verifying sources when engaging with AI.